A importância da educação socioemocional para os discentes no ensino médio integrado do IFPA Campus Itaituba - Campos, Cácia Samira de Sousa (Brasil, 2022)
The study addresses the development of socio-emotional education, based on educational processes that meet the socio-emotional needs of students. It aims to understand the importance of socio-emotional education for students in the Integrated High School of the Federal Institute of Education, Science and Technology of the State of Pará (IFPA), Itaituba Campus. The research site was the IFPA Itaituba Campus and the subjects of study were 13 students from technical high school courses. Through a qualitative approach, this study uses the questionnaire, focus group, observation and field diaries as data collection, in order to better understand the phenomenon researched. For data analysis, Discursive Textual Analysis (DTA) was used, which resulted in the metatext entitled “Paths to the practical meanings of school: the phenomenon of socio-emotional education”. The study indicates the phenomenon of socio-emotional education as a need to prepare for life, in view of the practical meanings of the school, which permeate knowledge ranging from the world of work to the appreciation of emotions and much more. The meanings identified lead to the perception of the need for a edagogical approach that contemplates the students in a holistic way, considering their anxieties, difficulties, profiles and real needs. It also highlights the context of Covid-19 pandemic, marked by social and emotional damage, which highlighted the gap in schools related to the lack of assistance and strengthening of mental health. Based on this information, an Educational Product was created in video format, entitled "Socio-emotional education from students’ perspectives", aimed to subsidize the school community on how to work with socio-emotional education in a meaningful way, considering different student contexts. Its purpose is to address the educational action as a broad process, as the academic performance and action in different real-life settings must be understood from a comprehensive perspective, considering, not only instrumental intelligence but also the ability to manage emotions, affections and social relations, in view of the commitment to Integral Human Training.